Adsorption and Regeneration of Indonesian Natural Pumice for Total Chromium Removal from Aqueous Solution - Indah, Shinta; Helard, Denny; Marchelly, Fitria; Putri, Dean Eka (Research Centre of Inorganic Materials and Complexs, 2018)
To investigate the potential of adsorption and regeneration of natural pumice from West Sumatera Indonesia for total chromium (Cr) removal from aqueous solution, batch experiments in multiple adsorption-desorption cycles were performed. The results indicated that the optimum condition of total Cr removal were 3 of pH solution, 0.3 g/L of adsorbent dose, 60 min of contact time of adsorption, <63 ?m of diameter of adsorbent, and 1 mg/L of total Cr initial concentration with 2.226 mg Cr/g pumice of total Cr uptake. The experimental data obtained were fitted with the Freundlich adsorption isotherm within the concentration range studied. Desorption efficiencies for total Cr ions by using 0.1 M HCl as desorbing agent were in the range of 31-32%. Although complete desorption were not attained, the natural pumice could be sufficiently reused up to 3 cycles of adsorption- desorption with increasing trend in total Cr uptake that may due to the surface modification of natural pumice caused by HCl. Overall results revealed that easy availability of natural pumice as local mineral in West Sumatra, Indonesia and its ability to adsorb and retain total Cr will create more interest to develop new natural adsorption method of pollutant removal from solution